OS 06-06 PREVALENCE AND CONSEQUENCE OF ORTHOSTATIC HYPERTENSION IN COMMUNITY DWELLING 85, AND 90 YEAR OLDS. (September 2016) - Bursztyn, Michael; Hammerman-Rozenberg, Aliza; Jacobs, Jeremy; Stessman, Jochanan
Abstract : Objective: To investigate the prevalence, characteristics, and association with mortality of orthostatic hypertension (OHYPER) amongst the oldest old. Design and method: Two waves from the Jerusalem Longitudinal Study of community dwelling residents born in 1920–21 were examined at age of 85 (n = 1004), and 90 (n = 437). Sitting blood pressure (BP) was measured three times on two occasions, averaged and compared to 1 minute standing BP. OHYPER, orthostatic hypotension (OHYPO) or normotension (ONT) were classified if the difference of standing–sitting SBP either increased or decreased by ≥20mmHg, or not. Mortality data between ages 85–95 and 90–95 were collected from Ministry of Interior registry. Results: Prevalence of OHYPO, ONT, OHYPER was 4.8 % (n = 48), 91% (n = 915), and 4.1% (n = 41) at age 85, and 8.9% (n = 39), 88.1% (385), and 3.0% (n = 13) at age 90. There was a tendency for fewer men among OHYPER, and significantly more subjects with financial hardship, higher weight, loneliness, and anemia (p < 0.05 for all) among the 85 year olds, and fewer with poor self rated health, and more with anemia among the 90 year olds. Sitting SBP was 157 ± 22/75 ± 11, 147 ± 21/74 ± 11, and 140 ± 16/74 ± 10 mmHg among OHYPO, ONT, and OHYPER at age 85 (p < 0.0001), and 166 ± 28/75 ± 10, 145 ± 24/70 ± 11, and 136 ± 23/74 ± 9 mmHg at age 90 (p < 0.0001), respectively. Ten years survival was 27%, 30%, and 27% respectively at age 85 (log-rank p = 0.34). Five years survival was, 57%, 67%, and 55% respectively at age 90 (long-rank p = 0.14). In an adjusted Cox proportional Hazards Ratio model, OHYPER at age 85 was not associated with mortality (HR = 0.95, 95% confidence interval 0.65–1.39). Male gender, physical inactivity, anemia, activities of daily living dependence, diabetes, and ischemic heart disease were significant mortality predictors. The few OHYPER among 90 year olds precluded modeling. Conclusions: OHYPER is quite uncommon among community dwelling 85 and 90 year olds, and unlike recent publications, is not associated with increased mortality.